Outcome and development of symptoms after orthotopic liver transplantation for Wilson disease - Weiss, Karl Heinz; Schäfer, Mark; Gotthardt, Daniel; Angerer, Alexandra; Mogler, Carolin; Schirmacher, Peter; Schemmer, Peter; Stremmel, Wolfgang; Sauer, Peter (Clinical transplantation, 2013)
Background Wilson disease (WD) is an autosomal recessive copper storage disease resulting in hepatic and neurologic dysfunction. Liver transplantation is an effective treatment for fulminant cases for patients with chronic liver disease. Reports on the outcome of neuropsychiatric symptoms after orthotopic liver transplantation (OLT) are limited. Aim To assess the course of neuropsychiatric and hepatic symptoms after liver transplantation for Wilson disease Methods Nineteen patients with Wilson disease received liver transplantation and were followed prospectively from 2005 to 2010 for the development of hepatic, neurological and psychiatric symptoms. Results Eight patients (all female) were transplanted for acute liver failure and eleven patients for chronic liver failure. Patient survival rates one and five yr after transplantation were 78% and 65%, respectively. Of the surviving patients, hepatic symptom scores improved in all patients and neurological symptom scores improved in all but one patient after OLT compared to the time of initial diagnosis and compared to pre-OLT status. Psychiatric symptoms showed moderate improvements. Conclusion Survival after OLT for Wilson disease with end-stage liver disease is excellent. Overall, neuropsychiatric symptoms improved after transplantation, substantiating arguments for widening of the indication for liver transplantation in symptomatic neurologic Wilson disease patients with stable liver function.
Gesehen am 28.10.2021